2015
DOI: 10.1371/journal.pone.0137670
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Morpholino Oligonucleotides Reduce Neurofilament Synthesis and Inhibit Axon Regeneration in Lamprey Reticulospinal Neurons

Abstract: The sea lamprey has been used as a model for the study of axonal regeneration after spinal cord injury. Previous studies have suggested that, unlike developing axons in mammal, the tips of regenerating axons in lamprey spinal cord are simple in shape, packed with neurofilaments (NFs), and contain very little F-actin. Thus it has been proposed that regeneration of axons in the central nervous system of mature vertebrates is not based on the canonical actin-dependent pulling mechanism of growth cones, but involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…S1A), whose regeneration probabilities have been determined previously (Jacobs et al ., 1997; Busch & Morgan, 2012). Interestingly, the large RS axons do not demonstrate collateral sprouting after spinal cord hemi-TX, but only true regeneration (Zhang et al ., 2015), and this, together with the ready regeneration after complete TX, allows us to study mechanisms of regeneration unambiguously. Moreover, after spinal cord TX many injured axon tips can be observed in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1A), whose regeneration probabilities have been determined previously (Jacobs et al ., 1997; Busch & Morgan, 2012). Interestingly, the large RS axons do not demonstrate collateral sprouting after spinal cord hemi-TX, but only true regeneration (Zhang et al ., 2015), and this, together with the ready regeneration after complete TX, allows us to study mechanisms of regeneration unambiguously. Moreover, after spinal cord TX many injured axon tips can be observed in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies from our lab and others’ showed that a very delayed form of retrograde neuronal death occurs in spinal-projecting neurons of the brain after SCI in lampreys (Shifman et al ., 2008; Busch & Morgan, 2012; Hu et al ., 2013; Zhang et al ., 2015). Similar phenomena have been reported in mammals (Mori et al ., 1997; Houle & Ye, 1999; Novikova et al ., 2000; Hains et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a control, we used a 5-base pair mismatch synuclein morpholino (MM MO). The lissamine-labeled morpholinos were loaded at the time and site of spinal transection, as is standard in zebrafish and lamprey SCI models (Becker et al, 2004; Zhang et al, 2015). Afterwards, fluorescence in the cell body indicated that the morpholinos were retrogradely transported to the RS neuron cell bodies, where they remained up to 11 weeks post-transection (Fig.…”
Section: Resultsmentioning
confidence: 99%